Analisis Puisi “Jarak 1” Karya Heri Isnaini Dengan Menggunakan Pendekatan Mimetik - Fitriana Fitriana (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Poetry is beautiful language based on the results of someone's thoughts and feelings expressed in written language. Poetry is an imaginative literary work that contains analogies of meaning with other uses so that the meaning contained in the poem is hidden behind words, similes and aesthetics that not everyone understands the meaning of the poetry conveyed. When reading poetry, it is necessary to read poetry repeatedly to understand the meaning of the poem because the language in poetry has a broad, implied meaning and is difficult to interpret. Therefore, readers must understand how to study poetry with knowledge in order to understand the meaning of the poetry conveyed. The poem by Heri Isnaini with the title